2020
DOI: 10.1002/ecs2.3078
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling local, metapopulation, and cross‐community sources of stabilization and asynchrony in metacommunities

Abstract: Asynchronous fluctuations of populations are essential for maintaining stable levels of bio-mass and ecosystem function in landscapes. Yet, understanding the stabilization of metacommunities by asynchrony is complicated by the existence of multiple forms of asynchrony that are typically studied independently: Community ecologists, for instance, focus on asynchrony within and among local communities, while population ecologists emphasize asynchrony of populations in metapopulations. Still, other forms of asynch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 49 publications
2
50
2
Order By: Relevance
“…Local insurance due to species diversity was shown to provide stronger stabilising effects on regional ecosystem functioning than did spatial insurance in a desert grassland ecosystem in New Mexico (Wang et al ., 2019 a ) and in a Californian kelp forest (Lamy et al ., 2019). Other studies, however, found that spatial insurance contributed more than did local insurance to the stability of benthic marine fish communities (Thorson et al ., 2018) and rock‐pool invertebrate metacommunities in Jamaica (Hammond et al ., 2020). More empirical work is required to quantify insurance effects from different sources and across scales and organisational levels and clarify how their relative importance changes with abiotic and biotic factors.…”
Section: Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Local insurance due to species diversity was shown to provide stronger stabilising effects on regional ecosystem functioning than did spatial insurance in a desert grassland ecosystem in New Mexico (Wang et al ., 2019 a ) and in a Californian kelp forest (Lamy et al ., 2019). Other studies, however, found that spatial insurance contributed more than did local insurance to the stability of benthic marine fish communities (Thorson et al ., 2018) and rock‐pool invertebrate metacommunities in Jamaica (Hammond et al ., 2020). More empirical work is required to quantify insurance effects from different sources and across scales and organisational levels and clarify how their relative importance changes with abiotic and biotic factors.…”
Section: Future Challengesmentioning
confidence: 99%
“…In particular, it has been expanded to include the spatial dynamics of biodiversity and ecosystem functioning and the role played by species dispersal in maintaining the benefits of biodiversity at large spatial scales – this is known as spatial insurance theory (Loreau, Mouquet & Gonzalez, 2003 a ). It has also inspired new methods to partition the buffering (Wang et al ., 2019 a ; Hammond et al ., 2020) and performance‐enhancing (Isbell et al ., 2018) effects of biodiversity across multiple scales in empirical data. Lastly, it has been applied in biodiversity and ecosystem management, and has even fed back into economics through the development of new approaches to quantify the insurance value of biodiversity (Baumgärtner, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In competitive metacommunities, changes in stability are linked to changes in synchrony. For example, asynchrony among populations of either different species (local-scale species synchrony) or different patches (species-level spatial synchrony) has been shown to stabilize competitive metacommunity dynamics through greater species diversity (Blasius et al, 1999, Wang et al, 2019, Hammond et al, 2020. Similarly, the insurance hypothesis predicts that species might exhibit temporal complementarity because of asynchronous responses to environmental fluctuations, resulting in community or metacommunity stability despite variable population dynamics (Loreau et al, 2003).…”
Section: Synchrony-stability Relationshipmentioning
confidence: 99%
“…Whereas local community stability is controlled by the stability of local populations and their compensatory dynamics, regional stability emerges from spatial asynchrony among populations connected by dispersal (i.e. metapopulations; Hammond et al, 2020; Larsen et al, 2021; Wang et al, 2019). Understanding how environmental change may erode local stability, and the scaling of local stability to higher levels of biological organization, has become a pressing research need (Erős et al, 2020; Patrick et al, 2021; Petsch, 2016; Walter et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, large‐scale environmental controls may be locally attenuated or exacerbated, allowing for a diversity of biological responses depending on local conditions (Bunnell et al, 2010; Cayuela et al, 2020; Hansen et al, 2019). Such diverse responses are key to preserving asynchronous dynamics and ecological rescue, that is, the capacity of colonists from thriving populations to repopulate impacted ones through dispersal (Brown & Kodric‐Brown, 1977; Hammond et al, 2020). Nevertheless, spatially coordinated environmental fluctuations have the potential to synchronize metapopulation dynamics across large scales, a phenomenon known as the ‘Moran effect’ (Moran, 1953).…”
Section: Introductionmentioning
confidence: 99%